Autism Spectrum Disorders in Iran - MOHAMMADI, Mohammad Reza; SALMANIAN, Maryam; AKHONDZADEH, Shahin (Iranian Journal of Child Neurology, 2011)
How to Cite this Article: Mohammadi MR, Salmanian M, Akhondzadeh Sh. Autism Spectrum Disorders in Iran. Iranian Journal of Child Neurology2011;5(4):1-9. Objective Autistic disorder, Asperger syndrome, and PDD-Not Otherwise Specified are subsets of autism spectrum disorders (ASDs), which are characterized by impairments in social communication and stereotyped behavior. This article reviews the prevalence, etiology, diagnosis, and treatment of ASDs in Iran. Materials & Methods We searched PubMed, ISI Web of Science, and 4 Iranian databases (IranPsych,IranMedex, Irandoc and Scientific Information Database (SID) to find Iranian studies on ASDs. The results of 39 investigations, comprising original, review and editorial articles; proceedings; and available dissertations were categorized by prevalence, etiology, diagnosis, and treatment. Conclusion Several preliminary investigations have been done to evaluate the prevalence of ASDs, and risk factors and effective variables have been studied with regard to etiology. The diagnostic evaluation of ASDs, especially based on EEG, and several pharmacological and behavioral interventions for ASD have been implemented in Iran. Mental health, stress levels, and personality characteristics were examined in the parents of children with ASDs, which were focused on mothers. References First MB, Frances A, Pincus HA. DSM-IV-TR: Handbook of differential diagnosis. United States of America:American Psychiatric Publishing; 2002. Parker S, Zuckerman B, Augustyn M. Developmental and behavioral pediatrics, 2 th ed. United States of America:Lippincott Williams & Wilkins; 2005. Howlin P. Autism and Asperger syndrome, 2 th ed. United States of America: Routledge; 2005. Mohammadi MR, Akhondzadeh S. Autism Spectrum Disorders: Etiology and Pharmacotherapy. Curr Drug ther2007; 2: 97-103. Newschaffer CJ, Croen LA, Daniels J, Giarelli E, GretherJK, Levy SE, et al. The epidemiology of autism spectrumdisorders. Annu Rev Public Health 2007; 28: 235-258. Zaroff CM, Uhm SY. Prevalence of autism spectrum disorders and influence of country of measurement and ethnicity. Soc Psychiatry Psychiatr Epidemiol 2011;published online. Baron-Cohen S, Scott FJ, Allison C, Williams J, Bolton P, Matthews FE, et al. Prevalence of autism-spectrum conditions: UK school-based population study. Br J Psychiatry 2009;194:500-509. Brugha TS, McManus S, Bankart J, Scott F, Purdon S, SmithJ, et al. Epidemiology of autism spectrum disorders inadults in the community in England. Arch Gen Psychiatry 2011; 68: 459-465. Prevalence of autism spectrum disorders - Autism and Developmental Disabilities Monitoring Network, United States, 2006. MMWR Surveill Summ 2009; 58: 1-20. Fombonne E. Epidemiology of pervasive developmental disorders. Pediatr Res 2009; 65: 591-598. Ehlers S, Gillberg C. The epidemiology of Asperger syndrome. A total population study. J Child Psychol Psychiatry 1993; 34: 1327-1350. Kadesjo B, Gillberg C, Hagberg B. Brief report: autismand Asperger syndrome in seven-year-old children: a totalpopulation study. J Autism Dev Disord 1999; 29: 327-331. Williams JG, Higgins JP, Brayne CE. Systematic reviewof prevalence studies of autism spectrum disorders. ArchDis Child 2006; 91: 8-15. Bernier R, Mao A, Yen J. Psychopathology, families, andculture: autism. Child Adolesc Psychiatr Clin N Am 2010;19: 855-867. Shamsi-pour M, Yonesian M, Mansouri A. Epidemiologyof autism: recent challenges in prevalence of autism andits risk factors. Journal of health and knowledge 2010; 5:133. Ghanizadeh A. A preliminary study on screening prevalence of pervasive developmental disorder in school children in Iran. J Autism Dev Disord 2008; 38:759-763. Nejatisafa AA, Kazemi MR, Alaghebandrad J. Autisticfeatures in adult population: evidence for continuity ofautistic symptoms with normality. Advanced in cognitivescience 2003; 5: 34-39. Khoushabi K, Pouretemad HR. Prevalence of pervasive developmental disorders according to gender in a sampleof Iranian children referred to treatment and rehabilitation centers. Journal of Hamedan University of Medical Sciences 2006;13: 58-60. Jannati M. Epidemiology of autism in exceptional studentsin Mashhd. MA thesis in psychology of exceptionalchildren field. Islamic Azad University of Birjand; 2001. Mansouri M, Chalabianlou GR, Malekirad AA, MosadedAA. The comparison of factors affecting the theory of mind development in autistic and normal children. Arak Medical University Journal 2011; 13: 115-125. Salmanian M. Visual memory of shapes and face in children with ASDs as compared to normal children. MS thesis in cognitive psychology. Institute for cognitive science studies; 2010. 22. Ghanizadeh A, Mohammadi MR, Sadeghiyeh T, Alavi Shooshtari A, Akhondzadeh S. Symptoms of Childrenwith Autism Spectrum Disorder, a Clinical Sample. Iran J Psychiatry 2009; 4: 165-169. Sasanfar R, Haddad SA, Tolouei A, Ghadami M, Yu D, Santangelo SL. Parental age increases the risk for autismin an Iranian population sample. Mol Autism 2010; 1:2. Abolfazli R, Mirbagheri SA, Zabihi AA, Abouzari M. Autism and Celiac Disease: Failure to Validate the Hypothesis of a Possible Link. Iranian Red Crescent Medical Journal 2009; 11: 442-444. Hamidi Nahrani M, Sedaei M, Fatahi J, Sarough Farahani S, Faghihzadeh S. Auditory brain stem responses in autistic children in comparison with normal children. Audiology 2008; 16: 16-22. Sheikhani A, Behnam H, Mohammadi MR, Noroozian M. Evaluation of Quantitative Electroencephalography in Children with Autistic Disorders in Various Conditions Based on Spectrogram. Iran J Psychiatry 2007; 3: 4-10. Niedermeyer E, Lopes da Silva F. Electroencephalography:Basic principles, clinical applications, and related fields,5th ed. Philadelphia: Lippincott Williams & Wilkins;2005. Sheikhani A, Behnam H, Mohammadi MR, Noroozian M, Mohammadi M. Detection of Abnormalities for Diagnosing of Children with Autism Disorders Using of Quantitative Electroencephalography Analysis. J MedSyst 2010. Noroozian M, Sheikhani A, Behnam H, Mohammadi MR. Abnormalities of Quantitative Electroencephalography inChildren with Asperger Disorder Using Spectrogram and Coherence Values. Iran J Psychiatry 2008; 3: 64-70. Ahmadlou M, Adeli H, Adeli A. Fractality and a wavelet-chaos-neural network methodology for EEG based diagnosis of autistic spectrum disorder. J Clin Neurophysiol 2010; 27: 328-333. Bahari Gharagoz A, Hassanpour A, Amiri SH. Social interactions and repetitive behavior of autistic and trainable mentally retarded children. Developmental Psychology 2010; 7: 39-47. Campbell M, Adams P, Perry R, Spencer EK, Overall JE.Tardive and withdrawal dyskinesia in autistic children: aprospective study. Psychopharmacol Bull 1988; 24: 251-255. Anderson LT, Campbell M, Adams P, Small AM, Perry R, Shell J. The effects of haloperidol on discrimination learning and behavioral symptoms in autistic children. J Autism Dev Disord 1989; 19: 227-239. Shattock P, Kennedy A, Rowell F, et al. Role of neuropeptides in autism and their relationships with classical neurotransmitters. Brain Dysfunct 1990; 3: 328-345. Campbell M, Schopler E, Cueva, J, Hallin A. Treatmentof autistic disorder. J Am Acad Child Adolesc Psychiatry1996; 35: 134-143. Tsia LY. Psychopharmacology in autism. Psychosom Med 1999; 61: 651-665. McCracken JT, McGough J, Shah B, et al. Risperidone in children with autism and serious behavioral problems. N Engl J Med 2002; 347: 314 -321. Posey DJ, McDougle CJ. The pharmacotherapy of target symptoms associated with autistic disorder and other pervasive development disorders. Harv Rev Psychiatry 2000; 4: 45-63. Levy SE, Hyman SL. Novel treatments for autistic spectrum disorders. Ment Retard Dev Disabil Res Rev2005; 11: 131-142. Akhondzadeh S, Fallah J, Mohammadi MR, Imani R, Mohammadi M, Salehi B, et al. Double-blind placebo controlled trial of pentoxifylline added to risperidone:effects on aberrant behavior in children with autism. Prog Neuropsychopharmacol Biol Psychiatry 2010; 34: 32-36. Akhondzadeh S, Tajdar H, Mohammadi MR, Mohammadi M, Nouroozinejad GH, Shabstari OL, et al. A double-blindplacebo controlled trial of piracetam added to risperidonein patients with autistic disorder. Child Psychiatry Hum Dev 2008; 39: 237-245. Rezaei V, Mohammadi MR, Ghanizadeh A, Sahraian A,Tabrizi M, Rezazadeh SA, et al. Double-blind, placebo controlled trial of risperidone plus topiramate in children with autistic disorder. Prog Neuropsychopharmacol Biol Psychiatry 2010; 34: 1269-1272. Akhondzadeh S, Erfani S, Mohammadi MR, Tehrani-Doost M, Amini H, Gudarzi SS, et al. Cyproheptadine in the treatment of autistic disorder: a double-blind placebo controlled trial. J Clin Pharm Ther 2004; 29: 145-150. Mohammadi MR, Asadabadi M, Akhondzadeh S. A double-blind placebo controlled trial of celecoxib added to risperidone in children with autistic disorder. Unpublished paper. Ghanizadeh A. Targeting of glycine site on NMDA receptor as a possible new strategy for autism treatment.Neurochem Res 2011; 36: 922-923. Ghanizadeh A. Targeting neurotensin as a potential novel approach for the treatment of autism. J Neuro inflammation 2010; 7: 58. Bahmanzadegan Jahromi M, Yarmohammadian A,Mousavi H. Efficacy of social skills training in autistic behaviors and social development in children with autism disorder through social stories. New findings inpsychology 2009; 3: 79-93. Dalvand H, Dehghan L, Feizy A, Hosseini SA. The effect of home based Lovaas approach on social interaction,Speech and language, Play and behavior skills, and intensity of autism in young children with Autism. Modern Rehabilitation 2009; 3: 3. Golabi P, Alipour A, Zandi B. the effect of intervention by ABA method on children with autism. Research on exceptional children 2005; 5: 33-54. Arman S, Hakiman S, Golabi P. Three therapeutic methods for autistic children: a clinical trial. Journal of Isfahan Medical School 2005; 23: 44-48. Hatamzadeh A, Pouretemad H, Hassanabadi H. The effectiveness of parent-child interaction therapy for children with high functioning autism. World Conferenceon Psychology, Counselling and Guidance 2010; 5: 994-997. 52. Chimeh N, Pouretemad HR, Khoramabadi R. Need assessment of mothers with autistic children. Journal of family research 2007; 3: 697-707. Ghanizadeh A, Alishahi MJ, Ashkani H. Helping families for caring children with autistic spectrum disorders. Arch Iran Med 2009; 12: 478-482. Khoushabi K, Farzad Fard SZ, Kakasoltani B, Pouretemad HR, Nikkhah HR. Coping strategies and stress in mothers with autistic children in comparison with mothers with normal children. Journal of family research 2010; 6: 87-97. Ghobari Bonab B, Estiri Z. A comparative study on personality characteristics and attachment style in mothers of children with and without autism. Research on exceptional children 2006; 6: 787-804. Rajabi Damavandi G, Poushineh K, Ghobari Bonab B. the relationship between personality characteristics and coping strategies in parents of children with ASDs. Research on exceptional children 2009; 9: 133-144. Samadi SA. Parents of children with autism spectrum disorder and children with intellectual disabilities and their stress and general health. Int J Integr Care2009; 9. Khoramabadi R, Pouretemad HR, Tahmasian K,Chimeh N. A comparative study of parental stress in mothers of autistic and non autistic children. Journal of family research 2009; 5: 387-399. 59. Poretemad HR, Khoushabi K, Afshari R, Moradi S. Coping strategies and mental health in autistic children mothers. Journal of family research 2006;2: 285-292. Mohammadi A, Pouretemad HR, Khosravi G. Aninitial examination of the effect of guided imagery via music on reduction of stress, depression, and anxiety of mothers with autistic children. Journal of family research 2005; 1: 289-303. Arman S, Zareei N, Farshid nejad AA. Efficacy of group counseling on mothers with autistic children. Research in Behavioral Sciences 2004; 2: 48-52.